Photoreceptor Diversification Accompanies the Evolution of Anthozoa. (23rd November 2020) - Gornik, Sebastian G; Bergheim, Bruno Gideon; Morel, Benoit; Stamatakis, Alexandros; Foulkes, Nicholas S; Guse, Annika
Abstract: Anthozoan corals are an ecologically important group of cnidarians, which power the productivity of reef ecosystems. They are sessile, inhabit shallow, tropical oceans and are highly dependent on sun- and moonlight to regulate sexual reproduction, phototaxis, and photosymbiosis. However, their exposure to high levels of sunlight also imposes an increased risk of UV-induced DNA damage. How have these challenging photic environments influenced photoreceptor evolution and function in these animals? To address this question, we initially screened the cnidarian photoreceptor repertoire for Anthozoa-specific signatures by a broad-scale evolutionary analysis. We compared transcriptomic data of more than 36 cnidarian species and revealed a more diverse photoreceptor repertoire in the anthozoan subphylum than in the subphylum Medusozoa. We classified the three principle opsin classes into distinct subtypes and showed that Anthozoa retained all three classes, which diversified into at least six subtypes. In contrast, in Medusozoa, only one class with a single subtype persists. Similarly, in Anthozoa, we documented three photolyase classes and two cryptochrome (CRY) classes, whereas CRYs are entirely absent in Medusozoa. Interestingly, we also identified one anthozoan CRY class, which exhibited unique tandem duplications of the core functional domains. We next explored the functionality of anthozoan photoreceptors in the model species Exaiptasia diaphana (Aiptasia), which recapitulates key photo-behaviors of corals. We show that the diverse opsin genes are differentially expressed in important life stages common to reef-building corals and Aiptasia and that CRY expression is light regulated. We thereby provide important clues linking coral evolution with photoreceptor diversification.